Health Knowledge Effects: An Integrated Community Health Promotion Platform. Issue 3 (March 2016) - Chang, I-Chiu; Lin, Chih-Yu; Tseng, Hsiao-Ting; Ho, Wen-Yu
Abstract : The Taiwanese government subsidizes healthcare providers offering preventive medicine to patients to help reduce the threats of chronic sickness and halt skyrocketing medical expenditures. Usually, nurses are the primary workers who perform community health promotion; however, because of the chronic shortage of working nurses, many Taiwan hospitals have closed wards and deferred the responsibility of promoting primary prevention. With a community health promotion platform integrating interactive response features and Web sites for community patients and hospital staff, a case hospital efficiently sustained the community health services. The objective of this study was to assess the impact of the integrated community health promotion platform for conducting education. Fifty-four patients/residents were invited to join a quasi-experiment of health education, and a follow-up survey was conducted to assess the acceptance of the community health promotion platform from both the experimental group of learners/users and the hospital staff. The results showed that the community health promotion platform was effective in improving participant health awareness. The experimental group outperformed the control group, with higher posttest scores and longer knowledge retention. Furthermore, users indicated a high acceptance of the community health promotion platform.